(untitled) (Revista Argentina de Musicología, 2012)
While dwelling in the USA, Béla Bartók was requested to compose a symphonic work under very difficult circumstances due to his illness and scant financial resources. Nobody expected him to finish the work. However, he accomplished the commission in less than two months. His Concerto for Orchestra was the product. It contains a movement entitled “Serenata Interrotta” which is distinguished by means a series of unique musical traits. It was thought to serve the parodic purpose of mocking, through a citation, a passage of Shostakovich’s Seven Shymphony. The discovery of certain testimonies could prove that the movement followed a sufficiently detailed programme. Were it to be trustworthy, it would lead to a new interpretation of the work. More complex ways of understanding it would open new visions. Not only the commonly assumed explanation has to be questioned, but also a subtler one must be set in motion in regard to the author´s purposes.